Fertirrigação em abobrinba italiana (Cucurbita pepo L.) conduzida em ambiente protegido - Maller, André (2012)
The zucchini is the eleventh largest vegetable crop production in Brazil, mainly in the southeast and south. The major producing states are Minas Gerais, São Paulo and Paraná. Growing zucchini in greenhouse production has advantages as constant year round and increase productivity. The protected cultivation is generally associated with drip irrigation and fertigation. The technique enables rational dosage of fertilizers, water savings, optimized crop nutrition, fertilization automation, increase yield and fruit quality. Moreover, the irrigation conducted inappropriately provides various problems such as soil salination and wastage of fertilizer, which may reduce productivity and decrease the viability of the production system. There is a need for information on fertigation so that you can adjust according to the management culture and the type of soil to increase profitability. This study aims to evaluate the growth pattern of the fruits of zucchini, provide tools for better enforcement of fertigation techniques in zucchini and set a model that allows predicting the weight of fruit in a nondestructive analysis.